Psychiatric morbidity in the first degree relatives of mood disorder patients - Varma, Shashjit Lal; Zain, Azhar Md; Singh, Suarn (1999)
The well known advances in molecular genetics have lent new importance to the evidence that the disorders are genetically transmitted, raising the hope that vulnerable individuals, rational and definitive treatments may be identified, based on the discovery of specific deficits.At the same time, epidemiological evidence points to a secular increase in mood disorders in recent decades that interacts with familial vulnerability, but also must include major non genetic causative factors.Twin and adoption studies show that vulnerability to a disorder has a genetic component.Family studies indicate in a particular population the degree to which a disorder is familial, which diagnostic entities or other characteristics share familial transmission with a particular disorder and perhaps most importantly, allow the testing of hypothesis regarding the mode of genetic transmission.